Highly Miniaturized Octa-band Antenna Using Concentric Circular Split Ring Structures - P, Padmaja Priyadarsini; DS, Chandu (International Journal of Electrical and Computer Engineering Systems, 2025)
The proposed antenna design represents a systematic evolution from a simple ring-shaped structure to a highly efficient and versatile multi-band configuration tailored for next-generation wireless communication systems. Through the integration of rectangular slots, circular-shaped split ring resonators (CSRRs), and optimized geometries, the antenna achieves octa-band operation with superior impedance matching, enhanced bandwidth, and improved performance over a wide frequency range. The antenna is designed to support communication bands, including 4G/3G/2G, Wi-Fi, WLAN, WiMAX, and sub-6 GHz 5G connectivity. It resonates at 1.22, 2.12, 3.00, 4.76, 5.40, 5.94, 6.70, and 7.44 GHz, with a compact electrical size of 0.08 λ0 × 0.08 λ0. The inclusion of CSRRs and slots significantly expands the operational frequency bands while achieving a radiation efficiency of 84% and a peak gain of 4.1 dBi, making it well-suited for modern wireless applications. Moreover, the antenna design simplifies manufacturing and reduces the costs. Its compact and efficient structure ensures seamless integration into portable devices such as tablets and laptops, addressing the challenges of system complexity, size, and cost. This antenna provides a practical and scalable solution to meet the demands of diverse frequency bands in modern communication systems.